The Influence Of Work Stress, Work Environment And Social Support On Employee Performance With Job Satisfaction As An Intervening Variable - Louwi Mussa; Pahlawansjah Harahap; Hardhani Widhistuti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Every employee in the organization is required to make a positive contribution through good performance, remembering that organizational performance depends on the performance of its employees. This research aims to identify the relationship between the influence of work stress, work environment and social support on the performance of employees at RSD K.R.M.T Wongsonego Semarang City through job satisfaction. The data analysis method used is descriptive analysis with a quantitative research type. The sampling technique uses stratified random sampling. This research involved 75 respondents. Data source from questionnaires or questionnaires collected via Google Form. The research results prove that the work environment has a positive effect on job satisfaction, social support has an effect on employee performance and job satisfaction acts as a mediator in the relationship between the work environment and employee performance, so this hypothesis is declared accepted. However, the job stress and social support variables partially do not affect job satisfaction. Work stress and work environment also partially have no effect on employee performance. Likewise, job satisfaction is unable to play a mediating role in the relationship between work stress and social support on employee performance. Improving the work environment through improving facilities by investing in improving work facilities such as comfortable break rooms, modern medical equipment, and a clean and safe work environment can increase job satisfaction. Creating a supportive work atmosphere can improve employee welfare. Hospitals should provide stress management training for employees to help them manage work stress better. Even though research shows work stress has no direct effect on performance, good stress management can improve general well-being.